Learning to Discern the Voices of Gods, Spirits, Tulpas, and the Dead. (25th February 2023) - Luhrmann, Tanya M; Alderson-Day, Ben; Chen, Ann; Corlett, Philip; Deeley, Quinton; Dupuis, David; Lifshitz, Michael; Moseley, Peter; Peters, Emmanuelle; Powell, Adam; Powers, Albert
Abstract: There are communities in which hearing voices frequently is common and expected, and in which participants are not expected to have a need for care. This paper compares the ideas and practices of these communities. We observe that these communities utilize cultural models to identify and to explain voice-like events—and that there are some common features to these models across communities. All communities teach participants to "discern, " or identify accurately, the legitimate voice of the spirit or being who speaks. We also observe that there are roughly two methods taught to participants to enable them to experience spirits (or other invisible beings): trained attention to inner experience, and repeated speech to the invisible other. We also observe that all of these communities model a learning process in which the ability to hear spirit (or invisible others) becomes more skilled with practice, and in which what they hear becomes clearer over time. Practice—including the practice of discernment—is presumed to change experience. We also note that despite these shared cultural ideas and practices, there is considerable individual variation in experience—some of which may reflect psychotic process, and some perhaps not. We suggest that voice-like events in this context may be shaped by cognitive expectation and trained practice as well as an experiential pathway. We also suggest that researchers could explore these common features both as a way to help those struggling with psychosis, and to consider the possibility that expectations and practice may affect the voice-hearing experience.